Applying Augmented Reality for Anatomy Teaching and Learning - Gritcharoen, Jiranda (Srinagarind Medical Journal, 2020)
Background and Objective : At present, communication technology has continue developing complexly. McLuhan stated that “Medium is a Message”. This term remind us to aware that “channel” in communication process has more important, even message is the same but changing communication channel makes change to message. Receiving 3D image by AR have to use device with digital camera attached e.g. smart phone or tablet. Applying AR for teaching and studying Anatomy is a routine to research contains 3 research questions. Firstly, can 3D image gain very attention from audience? Secondly, How many method to create 3D image for AR? Thirdly, can 3D image, which use AR as a tool, replace Anatomy text book? In this research, researcher build Application which present 3D skull image. Seven bones, i.e. 1) Frontal Bone, 2) Temporal Bone, 3) Occipital Bone, 4) Zygomatic Bone, 5) Nasal Bone, 6) Maxilla Bone and 7) Mandible Bone, were choosen to present in this research. The application base on Android Operation System. Method : Researcher used Trial-Error as a research method and used Focus Group interview to test effectiveness and gain opinion of samples which were 40 medical students, from second year students to interns medical students, also 5 Anatomy Lecturers were sampled by using simple random sampling from student and lecturer list. Questions were asked in Focus Group Interview were concerned interesting of AR Questions also about knowledge and understanding in Anatomy which appeared in Anatomy text book by using AR as the added on. Result : The results showed that samples want the skull can be turned 360 degrees via touch screen of device. Moreover, sample want to zoom in and zoom out via touch screen. For turning skull via touch screen, researcher have collected this function as sample had recommended. On the other hand, zooming in and zooming out are too much consume technology resources of device. By the way, researcher aimed to develop this application and this function in future. Interviewing samples showed that AR skull can be added on in Anatomy text book which gain more attention and interesting from audience. Conclusion : AR technology can’t replace Anatomy text book but, with AR, text book has more added value. Moreover, 3D image presented by AR technology, can provide wide perspective, high perspective and depth perspective, that ordinary 2D image in text book can’t present to readers.